Down’s syndrome and COVID-19: risk or protection factor against infection? A molecular and genetic approach - Altable, Marcos; De la Serna Tuya, Juan Moisés (Neurological sciences, 2021)
Down syndrome (DS) is the most common genetic cause of learning difficulties and intellectual disabilities. DS patients often present with several congenital defects and chronic diseases, including immunity disorders. Elevated levels of pro-inflammatory cytokines such as interleukin (IL)-6 and tumor necrosis factor alpha (TNF-α) have been seen, which appear to vary with age. At birth, patients present with combined immunodeficiency, with frequent infections that decrease with age. Furthermore, high levels of IL-4 and IL-10 with anti-inflammatory properties and low levels of IL-6 and TNF-α are described in children. The immune system is believed to play an essential role in SARS-CoV-2 pathogenesis, and it has been associated with elevated levels of pro-inflammatory cytokines and an exaggerated cytokine release syndrome (CRS) that may eventually trigger a severe situation called cytokine storm. On the other hand, genetic features seem to be involved in the predisposition to illness and its severity. Overexpression of DSCR1 and ZAKI-4 inhibits the translocation of activated T lymphocyte nuclear factor (NF-AT) to the nucleus, a main step in the inflammatory responsiveness. We discuss here the possible role of immunology and genetic features of DS in the infection and prognosis in COVID-19.
Keywords: cytokine storm; genetics; immunology; NF-AT; SARS-CoV-2; TNF-α; Scopus; JCR